P-274 Cycles with a high proportion of smooth endoplasmatic reticulum aggregates oocytes have a higher risk of transfer cancellation, but similar clinical outcomes after embryo transfer. (30th June 2022) - Spileers, A; De Croo, I; Degheselle, S; Stoop, D; Vanden Meerschaut, F
Abstract: Study question: Are the clinical outcomes of an ICSI cycle impacted by the proportion of oocytes with smooth endoplasmatic reticulum aggregates (SERa)? Summary answer: In terms of fertilization, blastocyst formation and live birth there is no difference between SERa- and SERa+ cycles, regardless of the proportion of SERa+ oocytes. What is known already: It is not certain yet whether the presence of oocytes with SERa may impact the clinical outcome of an ICSI cycle. The majority of studies compare the outcome of SERa positive (SERa+) versus SERa negative (SERa-) cycles. It is not clear whether the proportion of SERa+ oocytes may play a role on cycles overall outcome, and which patients are at risk of harvesting a higher proportion of SERa+ oocytes. Limited data suggests that the duration of stimulation, the total dose of gonadotropins, the serum hormone levels and the number of oocytes are positively correlated with the presence of SERa+ oocytes. Study design, size, duration: Retrospective study (2016-2019), including data from 2468 ovum pick-ups, performed in a tertiary university-based referral center. Results from fresh plus cryopreserved embryo transfers are included. In total, 2097 SERa- and 371 SERa+ cycles are included in the analysis. Participants/materials, setting, methods: Cases are categorized based on the rate of SERa+ oocytes compared to the total number of metaphase II oocytes: SERa- (N = 2097), low SERa + (<30%) (N = 262), and high SERa + (≥30%) (N = 109). Baseline patient characteristics, treatment cycle parameters and clinical outcome per cycle are compared between the groups. According to the local protocol, SERa+ oocytes are not used for ICSI. Main results and the role of chance: Women with high SERa+ proportion are older (36.15y for the SERa+ group vs. 34.49y for the high SERa- group, p < 0.001), have lower anti mullerian hormone levels (AMH) (1.60ng/ml vs. 2.28ng/ml, p < 0.001), received a higher total dose of gonadotropins (3227.01IU vs. 2858IU, p = 0.003), have fewer oocytes retrieved (9.13 vs. 11.08, p < 0.001), have a lower number of good quality day 5 blastocysts (1.17 vs. 2.33, p < 0.001) and face more often transfer cancellation (23.7% vs. 47.7%, p < 0.001). Compared to women with SERa- cycles, women with <30% SERa oocytes are younger (33.76y, p = 0.04), have higher AMH levels (2.56ng/ml, p < 0.001), have more oocytes retrieved (15.11, p < 0.001), have a higher number of good quality day 5 blastocysts (3.17, p < 0.001) and less transfer cancellations (14.9%, p < 0.001). A multivariate regression model adjusted for age, progesterone level at ovulation trigger and the type of pituitary suppression shows that cycles with a high proportion of SERa+ still have a lower amount of day 5 blastocysts (p < 0.001), a higher chance of transfer cancellation (p < 0.001), but no difference in the amount of retrieved oocytes (p = 0.097), fertilization (p = 0.813), blastocyst formation rate (0.975), implantation (p = 0.105) and live birth rate (p = 0.615). Limitations, reasons for caution: The SERa+ oocytes in this analysis were not used for ICSI, which could have affected the result between SERa+ and SERa- cycles. Wider implications of the findings: A low proportion of SERa+ oocytes (<30%) is common in young and high responders, without hampering clinical outcome. Contrary, >30% SERa+ oocytes leads to a higher risk of transfer cancellation, when these oocytes are not used for ICSI. Therefore, the inclusion of SERa+ oocytes for ICSI should be further investigated. Trial registration number: not applicable